Facing the pandemic with trust in science - Justin Sulik (Springer Nature, 2021)
Abstract How essential is trust in science to prevent the spread of COVID-19? People who trust in science are reportedly more likely to comply with official guidelines, implying that higher levels of adherence could be achieved by improving trust in science. However, analysis of a global dataset (n = 4341) suggests otherwise. Trust in science had a small, indirect effect on adherence to the rules. Nonetheless, it predicted people’s approval of prevention measures such as social distancing, and bridged political ideology and approval of the measures (conservatives trusted science less and in turn approved of the measures less). These effects were stronger in the USA than in other countries. Even though any increase in trust in science is unlikely to yield strong behavioural changes, given its relationships with both ideology and individuals’ attitudes to the measures, trust in science may be leveraged to yield longer-term sustainable social benefits.